PENGARUH KOMPETENSI PEDAGOGIK DAN KOMPOTENSI PROFESIONAL TERHADAP KINERJA GURU SMK NEGERI 1 KOTA JAMBI - Pascalia, Priska; Yudha, Redi Indra (Universitas Batanghari Jambi, 2021)
Abstract This study aims to (1) Know the general description of pedagogic competence, professional competence and teacher performance at SMK Negeri 1 Jambi City. (2) Knowing the importance of pedagogical competence on the performance of teachers in SMK Negeri 1 Jambi City. (3) Knowing the importance of professional competence on the performance of teachers in SMK Negeri 1Kota Jambi. (4) Knowing how much influence pedagogic competence and professional competence have on the performance of teachers in SMK Negeri 1 Jambi City.This research design uses quantitative research methods, with data collection techniques, through observation, interviews, and questionnaires. Where the population in this study were 109 teachers and a sample of 86 teachers. The research instrument test technique used in this study is the validity and reliability test, while the classical assumption test used is quantitative descriptive analysis, normality test, homogeneity test, linearity test, multicollinearity test, and multiple regression test.The results showed that: (1) pedagogical competence was included in the fairly good category with a TCR value of 68.03%, professional competence in the good category with a TCR value of 80.39%. (2) There is an effect of pedagogical competence on teacher performance with a tcount of 2.405 at a significant level of 0.018. (3) There is an effect of professional competence on teacher performance with a tcount of 2.897 at a significant level of 0.005. (4) pedagogical competence and professional competence have an influence on teacher performance which can be seen from the Ftable value of 6,552 with a significant value of 0.002. Thus, teacher performance is a description of the work done by educators with the tasks they carry out through pedagogical competences and professional competences that an educator must have.Keywords: Pedagogic Competence, Professional Competence, Teacher Performance